If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8 + z)(5z + 9) = 0 Reorder the terms: (8 + z)(9 + 5z) = 0 Multiply (8 + z) * (9 + 5z) (8(9 + 5z) + z(9 + 5z)) = 0 ((9 * 8 + 5z * 8) + z(9 + 5z)) = 0 ((72 + 40z) + z(9 + 5z)) = 0 (72 + 40z + (9 * z + 5z * z)) = 0 (72 + 40z + (9z + 5z2)) = 0 Combine like terms: 40z + 9z = 49z (72 + 49z + 5z2) = 0 Solving 72 + 49z + 5z2 = 0 Solving for variable 'z'. Factor a trinomial. (8 + z)(9 + 5z) = 0Subproblem 1
Set the factor '(8 + z)' equal to zero and attempt to solve: Simplifying 8 + z = 0 Solving 8 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + z = 0 + -8 Combine like terms: 8 + -8 = 0 0 + z = 0 + -8 z = 0 + -8 Combine like terms: 0 + -8 = -8 z = -8 Simplifying z = -8Subproblem 2
Set the factor '(9 + 5z)' equal to zero and attempt to solve: Simplifying 9 + 5z = 0 Solving 9 + 5z = 0 Move all terms containing z to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5z = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 5z = 0 + -9 5z = 0 + -9 Combine like terms: 0 + -9 = -9 5z = -9 Divide each side by '5'. z = -1.8 Simplifying z = -1.8Solution
z = {-8, -1.8}
| -2-3x+5=16+2x+22 | | .75x=.51 | | 8.5x-12=6.5x-18 | | (4z+5)(4+z)=0 | | 27y^3+36y^2+12y= | | y=6x^2+7x-10 | | 8.5x-12=6.5-18 | | 6-2x+8y+4x-15y= | | 1-t+2.2t=5.9 | | m^2+10m+41=0 | | 0.5(x+6)+1.5(x-5)= | | z^2-20=0 | | 3(1+h)=3h-9 | | 7y^2+12y=0 | | .8x=43 | | 3s^3-16s+5= | | 2x^2+4x+5=x | | -6y^2+53y+9= | | -.22x=.4 | | 32.31+31.32x=41.89 | | 2log^3x=log^3(x+6) | | 1.25x=3.75 | | 2xsquared+8=0 | | -10x^2+79x+8= | | 4x^2-28x+13=0 | | k*3(x-12)-3x=12 | | -7(m)=-42 | | P=a+b+4csolving | | p(5)=10-2q | | 6x=-2x-4.5 | | p-6=-9 | | x+.105x=35.7 |